Study of impact of assessment of estrogen receptor, progesterone receptor, Her2 neu receptor and Ki-67 at diagnosis in management of breast cancer patient at Birat Medical College Teaching Hospital (BMCTH) - Sharma, Shivraj; A, Rayamajhi; V, Ghosh; I, Sharma; S, Sapkota (Birat Journal of Health Sciences, 2024)
Introduction: Breast cancer is the most common cancer in Nepal. Treatment of breast cancer includes combined therapy based on hormonal receptors within breast tissue and is linked to prognosis and survival. Objective: To evaluate hormonal factors preoperatively and assess the impact of how it would change the management practices of treating breast cancer in our setup. Methodology: This descriptive prospective study was conducted from March to October 2023 in the department of surgical oncology BMCTH in patients with breast mass suggestive of carcinoma meeting inclusion criteria and willing for treatment. Patients demographic data, detailed history and clinical examination was done at the time of diagnosis entered in excel sheet and calculation done by SPSS. Ethical clearance was taken from the institutional review committee of BMCTH (Ref: IRC-PA-296/2023 ). Results: In 80 female patients with mean age 46.15 years, Left breast cancer (60%) was more common than right side (40 %). Most common site of presentation was the upper outer quadrant (UOQ- 47.%). Invasive ductal carcinoma was the commonest type (47.5%) of all histological variants. 67.5% patients had ER positive receptor, 67.5% had PR positive and 2 Her2 neu was present in 28.7 %. TNBC reported 18.75% (15 patients out of 80 patients). Ki- 67 prognostic value ranged from 10 to 70 with mean 29.91+-20.795%. Among all 36.3% underwent neoadjuvant chemotherapy prior to surgery and 63.7% underwent upfront surgery for breast cancer. Conclusion: Screening of Triple negative and luminal type B breast cancers preoperatively is essential. Evaluation of hormonal factors ER, PR, Her 2 neu and Ki-67 preoperatively is must as it changes the management practices of treating breast cancer.